Natural Medicines Database Review. Issue 3 (2nd July 2016) - Espe, Sue
ABSTRACT: Natural Medicines is a subscription, web-based database created for clinicians, pharmacists, allied health practitioners, and laypersons to find reliable information about complementary, alternative, and integrative medicine topics. Evidence-based monographs incorporate detailed information about product manufacturers, natural ingredients, and therapies. The database provides online interactive clinical tools, patient education materials, continuing education, and noteworthy news.